Pengaruh Growth Opportunity, Profitabilitas, Tingkat Likuiditas Terhadap Struktur Modal Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Elvina Kurniawati Hadiyanto dan Indra Widjaja (Universitas Tarumanagara, 2019)
This study aims at testing the influence of growth opportunity, profitability and liquidity level to the company’s capital structure particularly on food and beverage companies. This study used multiple regression analysis. The sample of this study were ten food and beverage companies listed on the Indonesian Stock Exchange from 2014-2016. This study used purposive sampling. The independent variables were the growth opportunity, profitability and liquidity level. The growth opportunity was measured using ROA and the liquidity level was measured using Current Ratio (CR). The dependent variable was the company’s capital structure measured by Debt Ratio (DR). The data showed that the growth opportunity, profitability and liquidity level gave negative effects to the company’s capital structure. The value of Growth Opportunity was -0.008. This means that growth opportunity had negative effect to the capital structure 0.8%. The value of Return on Asset was -0.770. This means that profitability level had negative effect to the capital structure 77%. The value of Current Ratio was -0.056, which means that the liquidity level had negative effect on the capital structure 5.6%.